STATUS HUKUM ANAK LUAR KAWIN BERDASARKAN HUKUM WARIS ISLAM DAN KITAB UNDANG-UNDANG HUKUM PERDATA - , Erla Pratidina ([Yogyakarta] : Universitas Gadjah Mada, 2012)
According to Islamic Law or Code of Civil Law, children conceive outside a marriage has different status compare to children conceive from a marriage. The difference is caused by legal status of the marriage. It seems that children conceive from outside a marriage is becoming an issue in Indonesia, although formally there are laws that regulate that. Misconception is often happened between society understanding and legal aspects because these two aspects states different opinions. The purpose of this research is to investigate the status of children conceives outside a marriage based on Islamic Law and Code of Civil Law and to understand the right of inheritance for those children based on the two laws. This research is normative juridical considering that the research is based on law and regulations, and also literature study. The source of literature study is coming from primary legal material (Bahan Hukum Primer) and secondary legal material (Bahan Hukum Primer). The methodology of this research is literature study. The analysis is conducted qualitatively using qualitative measures. The results of the research show that there is no difference in terms of the relation of children conceives from outside a marriage with their mother. Both a stated that that the children will only have legal relations with the mother. Meanwhile, in terms of the relation with the father, there are different between the two laws. According to Islamic Law, children conceive outside marriage cannot be related (nasab) to the father or the family of the father since in Islam, admittance is not known. On the other hand, according to the Code of Civil Law, children conceive outside marriage have the possibility to be related to the father as long as the father admit the children as theirs. Related to the rights of inheritance, Islamic Law states that the children conceive outside marriage do not have any rights from the fatherâs inheritance. Meanwhile, according to Code of Civil Law, these children will have the rights of inheritance as long as the childrenâs are already admitted by the fathers. In Civil Law, this matter is regulated in Chapter XII Section III Book II, Article 862 to Article 873 Code of Civil Law.